Investigation of TRPM7 Immunoreactivity as a Biomarker to Predict Treatment-Resistant Endometrial Hyperplasia: A Retrospective Case-Control Study - Haliscelik, Mesut Ali; Atilgan, Remzi; Pala, Sehmus; Artas, Gokhan; Kuloglu, Tuncay (Turkiye Klinikleri, 2023)
Objective: In our study, we investigated transient receptor potential melastatin 7 (TRPM7) immunoreactivity in pre- and posttreatment pathology samples of patients with endometrial hyperplasia (EH) who responded to progesterone therapy and were resistant to progesterone therapy. Material and Methods: In this retrospective, comparative and single-center case-control study, endometrial tissue TRPM7 immunoreactivity was evaluated in sections obtained from paraffin blocks of 60 cases diagnosed with EH and proliferative endometrium. Randomly selected proliferative endometrium group for control [(Group( G)1, n=20)], The first [(G2, n=20)] and second [(G3, n= 20)] biopsy results of the group diagnosed with EH and recovered with progesterone therapy. The first [(G4, n=20)] and second [(G5, n=20)] biopsy results of the group that was diagnosed with EH but did not recover with progesterone treatment. SPSS version 22 program (SPSS Inc., Chicago, IL) was used for statistical analysis. Intergroup evaluation was carried out with one-way ANOVA and post-hoc tukey test. p<0.05 values were considered statistically significant. Results: TRPM7 immunoreactivity was found to be significantly increased in G2, G4, and G5 compared to G1. However, no significant difference was observed between G2, G4, and G5. When compared with these groups, TRPM7 immunoreactivity was observed to be significantly decreased in G3, and it was observed to be similar to G1. Conclusion: In EH cases, the unchanged TRPM7 immunoreactivity before and after treatment may be an immunohistochemical biomarker for determining resistance to progesterone therapy.
Keywords: Biomarker; endometrial hyperplasia; immunohistochemistry; TRPM7